PENGARUH CAPITAL ADEQUACY RATIO DAN NON PERFORMING LOAN TERHADAP KINERJA KEUANGAN PERBANKAN YANG TERDAFTAR DI BEI - Febriana, Ramadhana; Efriyenti, Dian (LPPM Universitas Putera Batam, 2019)
This research have purpose to find out the influence give by capital adequacy ratio and non performing loan to banking financial perfomance which have been listed in Indonesia Stock Exchange (IDX). The population in this research is 43 banking companies which have been listed in Indonesia Stock Exchange (IDX) and there 20 companies which have been meet the criteria samples selected. The financial statement data have been obtained from IDX Batam representative. The research result by F test show that have significant influence which mean that simultaneously capital adequacy ratio and non performing loan give significant influence to Return On Assets, therefore the regresion model of this research are feasibel to be observed. Partially, by using t test it have been obtained that capital adequacy ratio variable not have any significant influence to return on assets, meanwhile the non performing loan variable have significant influence to return on assets.